Budaya Pengambilan Keputusan Organisasi : (Studi Kasus di Sekolah Menengah Pertama Swasta Kabupaten Situbondo) - Lukman Nul Hakim; Ahmad Musaddad (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
The progress of an educational institution cannot be separated from the influence and power of leadership which in this case is the principal. Leadership is an important scientific discipline that must be possessed by a leader so that he can apply the concept of leadership well. One of the important elements in leadership theory is making the right decisions so that later they have effective implications. This research was conducted in a private junior high school in Situbondo district, with the aim of understanding and obtaining an objective, factual, accurate and systematic picture of the problems in the research object. Data about the object of this study were obtained by means of observation, interviews and documentation of the decision-making patterns that exist in the private junior high school in making decisions. The research method uses qualitative research. From the results of the discussion obtained from the research, it can be concluded that the decision-making culture in the junior high school which is the location of this research has a characteristic, namely the uniformity of understanding that a decision-making must always be determined in an official meeting forum involving all education personnel. But of course in this case the researcher does not provide a justification but only provides an overview of the phenomenon of decision making in a private junior high school in Situbondo district.